A new species of short-fingered geckos Stenodactylus (Squamata, Geckonidae) from South Iran with taxonomic notes on validity of the genus Trigonodactylus Hass, 1957 - Nazarov, Roman A.; Melnikov, Daniel A.; Radjabizadeh, Mehdi; Poyarkov, Nikolay A. (Zootaxa, 2018)
In the present study we provide evidence for the validity of the genus Trigonodactylus Hass, 1957, improve the diagnosis for this genus and describe a new species that belongs to it—Trigonodactylus persicus sp. nov., from the sand dunes in Khuzestan Province, southwestern Iran. The new species is closely related to Trigonodactylus [Stenodactylus] arabicus sensu Hass, and can be distinguished by the following morphological characteristics: small size, maximum SVL 34 mm; SVL/TailL—approximately 1:1; ventral scales roundish, weakly keeled, 54–61 longitudinal rows at midbody and 190–25 along midbody. No enlarged postmentals. Fingers and toes slightly flattened dorso-ventrally. Lateral edge of digits fringed by series of projecting triangular scales. No web between digits. No preanal and femoral pores. Dorsal color pattern formed by thin, dark, irregular vermicular patches and spots. Sometimes these dark dorsal patterns blend with each other and form transverse bands. There is a narrow, dark, longitudinal line between forelimbs and hindlimbs on lateral sides. Dark, well developed ʌ-shaped marking on snout, which continues behind orbit on tympanum region, approaches the upper ear opening and ends on the pectoral arch. Labial scales white, in some cases with grey-brown dots. Dorsal surfaces of limbs and digits with irregular dark bands. Dorsal surface of tail with 8–10 wide, dark brown bands with irregular margins, same size as alternating light bands. Ventral surface of body and limbs white, tail with dark spots that become more distinct posteriorly.